Development of a Tailored Sol-Gel Immobilized Biocatalyst for Sustainable Synthesis of the Food Aroma Ester n-Amyl Caproate in Continuous Solventless System - Corina Vasilescu; Cristina Paul; Simona Marc; Iosif Hulka; Francisc Péter (Foods, 2022)
This study reports the synthesis of a hybrid sol-gel material, based on organically modified silanes (ORMOSILs) with epoxy functional groups, and its application in the stabilization of lipase type B from Candida antarctica (CalB) through sol-gel entrapment. The key immobilization parameters in the sol-gel entrapment of lipase using epoxysilanes were optimized by the design of numerous experiments, demonstrating that glycidoxypropyl-trimethoxysilane can allow the formation of a matrix with excellent properties in view of the biocatalytic esterifications catalyzed by this lipase, at an enzyme loading of 25 g/mol of silane. The characterization of the immobilized biocatalyst and the correlation of its catalytic efficiency with the morphological and physicochemical properties of the sol-gel matrix was accomplished through scanning electron microscopy (SEM), fluorescence microscopy (FM), as well as thermogravimetric and differential thermal analysis (TGA/DTA). The operational and thermal stability of lipase were increased as a result of immobilization, with the entrapped lipase retaining 99% activity after 10 successive reaction cycles in the batch solventless synthesis of n-amyl caproate. A possible correlation of optimal productivity and yield was attempted for this immobilized lipase via the continuous flow synthesis of n-amyl caproate in a solventless system. The robustness and excellent biocatalytic efficiency of the optimized biocatalyst provide a promising solution for the synthesis of food-grade flavor esters, even at larger scales.